Marissa Collection Online System (MCOS) / Mohd Hariz Marzuki - Marzuki, Mohd Hariz (2018)
Unlike in a traditional store environment where product is directly visible to customers, Internet retailers can selectively choose how to divulge product information. For example, when viewing a particular item, online shoppers may either see the details of the product or product physical appearances. By choosing the appropriate information-level cue to display by using system, customer can selectively see all information regarding the product to be there. In this report, we analyze the appropriate structure of system that can be used to help the organization. Consumers may potentially face a changes made regarding the process of buying and selling. We show that there are many ways out there that the process could still take in place, not in usually physical ways. Even though the process was totally different, with the current advancement of technology itself, the transformation of the process from physical into digital was possible. We also extend the model to consider the ease-of-use of process to customers, and thus highlight the advancement of technology could still support the daily process of buying and selling.